2022
DOI: 10.1099/ijsem.0.005181
|View full text |Cite
|
Sign up to set email alerts
|

Arthrobacter sunyaminii sp. nov. and Arthrobacter jiangjiafuii sp. nov., new members in the genus Arthrobacter

Abstract: Four novel bacterial strains (zg-ZUI122T/zg-ZUI10 and zg-ZUI227T/zg-ZUI100) were isolated from the intestinal contents of Marmota himalayana and characterized using a polyphasic approach. Cells were Gram-stain- and catalase-positive, urease- and oxidase-negative. Strains grew optimally at 28–30 °C, pH 7.0, with 0.5 % NaCl (w/v). A comparative analysis of 16S rRNA gene sequences revealed that strain pairs zg-ZUI122T/zg-ZUI10 and zg-ZUI227T/zg-ZUI100 belonged to the genus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 35 publications
(73 reference statements)
0
21
0
Order By: Relevance
“…Growth of all novel strains was excellent aerobically but strains zg-Y462 T /zg-Y411 and zg-Y453 T /zg-Y324 managed to survive and slowly grow under anaerobic conditions, different from zg-Y 809 T /zg-Y786. Identical with some species in the genus Arthrobacter such as A. sunyaminii zg-ZUI122 T [9], we observed that the three novel type strains (zg-Y453 T / zg-Y462 T /zg-Y809 T ) showed obvious rod-coccus cell cycles by transmission electron microscopy after culturing 1 and 4 days under the optimal growth conditions (Fig. S7).…”
Section: Phenotypic and Biochemical Characteristicsmentioning
confidence: 57%
See 4 more Smart Citations
“…Growth of all novel strains was excellent aerobically but strains zg-Y462 T /zg-Y411 and zg-Y453 T /zg-Y324 managed to survive and slowly grow under anaerobic conditions, different from zg-Y 809 T /zg-Y786. Identical with some species in the genus Arthrobacter such as A. sunyaminii zg-ZUI122 T [9], we observed that the three novel type strains (zg-Y453 T / zg-Y462 T /zg-Y809 T ) showed obvious rod-coccus cell cycles by transmission electron microscopy after culturing 1 and 4 days under the optimal growth conditions (Fig. S7).…”
Section: Phenotypic and Biochemical Characteristicsmentioning
confidence: 57%
“…S6), a glycolipid defined as monogalactosyldiacylglycerol by Busse [2] was present in strains zg-Y462 T , zg-Y809 T (labelled as GL1 in Fig. S6e, i), A. citreus DSM 20133 T and A. sunyaminii zg-ZUI122 T [9] but absent in strain zg-Y453 T (Fig. S6a), A. gandavensis JCM 13316 T , A. jiangjiafuii zg-ZUI227 T and A. yangruifuii 785 T [9][10][11]; also of note was that strain zg-Y809 T lacked lipid (Fig.…”
Section: Chemotaxonomic Datamentioning
confidence: 97%
See 3 more Smart Citations